Defining Development. C.R.R.S. Applied Series, Number 2. Special Issue. Development Praxis - Lackey, Alvin S.; Guelph Univ. (Ontario). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
A sampling of definitions indicates a certain amount of ambiguity and confusion about development and how it differs from other concepts such as growth and change. Any attempt to clarify this concept should begin initially with identification of the essential meaning of the term and then consideration of its characteristics and how it differs from other related concepts. A possible definition is development as a self-generating process whereby human potentials and relationships are optimized for the purpose of satisfying needs within the context of changing belief and value systems of a cultural unit and the larger human community. Some implications of this definition of development should be noted. First, if development takes place within the context of changing belief and value systems, then one must know what these beliefs and values are and how they are changing. Second, for meaningful development to occur, it must be implemented with the full participation of the people at the local level. Third, development is not comparative except for cultural units that have similar belief and value systems. (YLB)
ERIC Note: Document contains some broken type.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Community Development; Definitions; Development; Economic Progress; Individual Development; Social Development; Information Analyses